Teaching Machines Versus Lectures in Accounting Education: An Experiment. - Streuling, G. Fred; Holstrum, Gary L. (The Accounting Review, 1972)
Abstract ABSTRACT The relative effectiveness of a teaching machine and conventional lectures was studied in a controlled experiment in a portion of a tax accounting course. The nature of the teaching machine, the teaching problem, and the experimental design and controls are discussed. Subject to the limitations described, the results indicated that the lecture method provided greater immediate understanding, but that the teaching machine provided greater retention.